Pelatihan Membaca Syair Melayu di SMK Kelapa Sawit Arsya Ganeeta Indonesia sebagai Upaya Pelestarian Sastra dan Budaya Melayu - Hidayat, Rian; Siswanto, Siswanto; Nelfita, Yulia; Islami, M. Fiqri Al; Aulia, Windi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Malay poetry (syair) is a cultural heritage rich in aesthetic, moral, and social values. However, interest among younger generations in syair has declined due to the dominance of popular culture and the lack of interactive learning methods. At Arsya Ganeeta Indonesia Palm Oil Vocational School, students were found to have low levels of understanding, reading skills, and confidence in performing syair. To address these issues, a practice-based poetry reading training was conducted using an experiential learning approach. Data were collected through observations, interviews, and pre- and post-training questionnaires involving 28 students. The results showed significant improvements: understanding of syair increased from 11% to 86%, accurate pronunciation improved from 14% to 57%, appropriate use of tone and intonation rose from 11% to 50%, and students’ confidence in reading aloud grew from 11% to 54%. Additionally, 90% of participants expressed that the training was beneficial and hoped it would be continued. This training proved effective as an applicable culture-based learning model and can be integrated into local content curriculum or extracurricular activities to preserve Malay literary heritage among vocational school students.